Temperament as a Risk Factor for Clinical Diagnosis During the Transition From Childhood Through Adolescence and Young Adulthood: A 16-Year Multimethod Longitudinal Study - Nicole E. Lorenzo; Hong N. T. Bui; Selin Zeytinoglu; Kathyrn A. Degnan; Heather Henderson; Daniel S. Pine; Nathan A. Fox; Andrea Chronis-Tuscano (Clinical Psychological Science, 2026)
Identifying early temperamental predictors of later psychopathology is crucial for detecting at-risk individuals and implementing targeted prevention efforts. However, there is limited research using laboratory-based observations of temperament and “gold-standard” assessments of psychiatric disorders across early adolescence and young adulthood. Using a multimethod, prospective longitudinal study ( N = 291), we investigated whether temperament (i.e., behavioral inhibition [BI], exuberance) observed at 24 and 36 months predicted the likelihood of psychiatric disorders across adolescence/young adulthood. Results suggested that early childhood BI was not predictive of anxiety diagnosis over time; however, exuberance predicted attention-deficit/hyperactivity disorder at ages 12, 15, and 18 years. Results add to prior work that has rarely found direct relations between early temperament and psychopathology and highlight early adolescence/young adulthood as a vulnerable time for the development of psychopathology.